Fate of antibiotics from swine wastewater in constructed wetlands with different flow configurations. (May 2019) - Liu, Lin; Li, Jie; Fan, Hongyong; Huang, Xu; Wei, Lili; Liu, Chaoxiang
Abstract: The removal efficiencies and accumulated concentrations of oxytetracycline and ciprofloxacin in three pilot-scale constructed wetlands (CWs) with different flow configurations (surface, horizontal subsurface, and vertical subsurface flow) were investigated. The results indicated that the average mass removal efficiencies of the CWs for the target antibiotics in one year of treatment ranged from 85 to 99%, and the vertical subsurface flow constructed wetlands exhibited the highest and most stable removal efficiencies for oxytetracycline (99 ± 0.27%) and ciprofloxacin (97 ± 0.26%). The influence of seasonal changes on the removal efficiencies of oxytetracycline and ciprofloxacin in CWs was insignificant. The higher accumulated antibiotic concentrations and antibiotic-degrading bacteria abundances indicated that substrate adsorption and biodegradation were the predominant pathways affecting the antibiotic removal efficiency of wetlands. The concentration of accumulated ciprofloxacin in soil and oyster shell (84–124 and 83–115 μg kg −1 ) was significantly higher than that of oxytetracycline (37–81 and 3–17 μg kg −1 ). In addition, analysis results based on pilot-scale CWs also indicated that the influence of the type of CW on the bacterial community was more significant than the wetland substrate and residual concentration of antibiotics. Highlights: Flow configuration determine removal efficiencies of OTC and CIP in wetland. Removal rate of antibiotic in wetland increased in following order: VSF > HSF > SF. Neutral-pH level of substrate can enhance degradation rate of OTC in wetland. Flow configuration show more effect on bacterial community in CW than antibiotic.